A prospective observational study on cystic stump closure during laparoscopic cholecystectomy: silk sutures (intra-corporeal ligation) or locking clips (Hem-o-Lok®) - Yeni, Mustafa; Kalaycı, Tolga (The European Research Journal, 2022)
Objectives: The present study compares the clinicopathological features and outcomes of two cystic stump closure techniques (locking clips and intra-corporeal ligation with silk sutures) during laparoscopic cholecystectomy. Methods: This study was conducted in a tertiary health centre as a prospective observational study between October 5, 2021, and February 15, 2022. For randomisation, double rows of silk sutures were used to close the cystic stump in patients on the odd-numbered day of the month (Group 1). In contrast, a single-row locking clip (Hem-o-Lok®) (Group 2) was used to close the cystic stump in patients on the even-numbered day of the month. The study was terminated when at least 50 patients were reached in both groups. The clinicopathological differences and cholecystectomy outcomes were compared between the groups. Results: This observational study included 114 patients. Of the study cohort, 87 (76.3%) were female, and the mean age was 46.54 ± 14.74 years. There were 64 (56.1%) patients in Group 1 and 50 (43.9%) patients in Group 2. Preoperative ERCP requirement was higher in Group 1 (15.6% vs 4%, p = 0.045), while the mean operation room time was longer in Group 2 (p = 0.015). Morbidity rates were similar in the two groups (3.1% vs 2%) (p > 0.05). Conclusions: Cystic stump closure is the essential step of laparoscopic cholecystectomy. According to the present study’s results, silk sutures (intra-corporeal ligation) and locking clips (Hem-o-Lok®) are materials that can be used safely to close a cystic stump.